Forming preparation method of carbon monoxide selective oxidation catalyst
Through a new molding preparation method, the strength and molding rate of carbon monoxide selective oxidation catalyst are successfully improved by using celite powder and phthalidite powder as binders, and the existing catalysts are solved in the methanol fuel cell system. Various problems and exhibit efficient catalytic activity in CO selective oxidation reaction.
Patent Information
- Application Number
- CN202411365326.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-11
AI Technical Summary
The existing CeO2-based catalysts have problems such as large dust filling, difficulty in separation and recovery, large reactor pressure drop, severe emission carrying, low catalyst strength and small bulk density in methanol fuel cell systems. The extrusion process is complicated and the forming catalyst strength is Low.
A molding preparation method including the following steps: mix the carbon monoxide selective oxidation catalyst, cyanine powder and water to obtain a mixed material; mix the supradiate aluminite powder and an inorganic acid solution to obtain a binder; Mixed with the mixed material to obtain a catalyst precursor; the catalyst precursor is then extruded, dried and calcined to obtain a molded catalyst.
The method is simple to operate, has a high molding rate, and has high strength of the catalyst, which can be applied to complex environments, and exhibits efficient catalytic activity in CO selective oxidation reaction.
Smart Images

Figure BDA0005066700880000091 
Figure BDA0005066700880000101 
Figure HDA0005066701070000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a molding preparation method for a carbon monoxide selective oxidation catalyst. Background Art
[0002] A fuel cell is a highly efficient energy conversion device that can directly convert chemical energy stored in fuel and oxidant into electrical energy, and the energy conversion efficiency can reach more than 60%, which is much higher than the 30% of an internal combustion engine, and there is no pollutant emission. Therefore, the power system and distributed energy supply system with fuel cells as the core are considered to be one of the most attractive forms of terminal energy utilization in the 21st century. Among them, the proton exchange membrane fuel cell (PEMFC) has the most obvious advantages, but the material of its working electrode is mostly Pt metal, which is extremely sensitive to CO and can be easily deactivated by CO poisoning. Therefore, pure hydrogen (CO content less than 0.2ppm) is usually required as fuel.
[0003] At present, the main method of producing industrial hydrogen is to produce hydrogen through methanol reforming. The hydrogen produced contains 0.5-2% CO, 10-20% water and 20% CO2 gas, which needs to be purified. There are two main methods for removing CO: chemical method and physical adsorption method. Among them, the CO selective oxidation technology in the chemical method has the advantages of simple process, economy and high efficiency.
[0004] In the actual application of methanol fuel cells, the molding of catalysts is a key step. In the history of catalyst development around the world, a considerable number of catalysts did not end up being commercialized due to problems with molding technology. CeO2-based catalysts have received widespread attention in carbon monoxide selective oxidation systems due to their good oxygen transfer ability and good noble metal active sites. At present, the CO selective oxidation system in industrial methanol fuel cell systems is a fixed bed, which has very stringent requirements on the physical properties of the catalyst. Most of the current CeO2-based catalysts are in powder form, which have problems such as large dust loading, difficulty in separation and recovery, large reactor pressure drop, serious emission carryover, low catalyst strength, and low bulk density. At present, the commonly used molding method is extrusion molding, but the technical disadvantages of existing extrusion molding are low strength of the molded catalyst and complex extrusion process.
[0005] Therefore, it is a problem to be solved to provide an extrusion method with simple operation, high forming rate and high catalyst strength. Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide a molding preparation method for a carbon monoxide selective oxidation catalyst. The molding preparation method provided by the present invention is simple to operate, has a high molding rate, and the obtained catalyst has high strength.
[0007] The present invention provides a method for preparing a carbon monoxide selective oxidation catalyst, comprising the following steps:
[0008] A) mixing a carbon monoxide selective oxidation catalyst, sesbania powder and water to obtain a mixed material;
[0009] B) mixing pseudo-boehmite powder and an inorganic acid solution to obtain a binder;
[0010] C) mixing the binder with the mixed material to obtain a catalyst precursor;
[0011] D) extruding the catalyst precursor into a molded catalyst, drying and calcining the catalyst precursor to obtain a molded catalyst.
[0012] Preferably, the carbon monoxide selective oxidation catalyst is selected from Pt / CeO2 catalyst.
[0013] Preferably, the mass ratio of the carbon monoxide selective oxidation catalyst to the sesbania powder is 1:(0.01-0.05), and more preferably 1:0.03.
[0014] Preferably, the mass ratio of the carbon monoxide selective oxidation catalyst to water is 1:(0.1-0.25), preferably 1:0.15.
[0015] Preferably, the inorganic acid solution is hydrochloric acid, nitric acid, or sulfuric acid, preferably nitric acid;
[0016] The nitric acid concentration is 0.1-3 mol / L, preferably 0.3 mol / L.
[0017] Preferably, the mass ratio of the pseudo-boehmite powder to the inorganic acid solution is 1:(0.05-1), and the preferred ratio is 1:0.1.
[0018] Preferably, the mass ratio of the mixture to the binder is 1:(0.1-0.5), and the preferred ratio is 1:0.2.
[0019] Preferably, the drying temperature is 30-100°C, preferably 50°C.
[0020] Preferably, the calcination temperature is 400-700°C, preferably 500°C; the heating rate is 0.5-3°C / min, preferably 1°C / min, and the calcination time is 2-6h, preferably 3h.
[0021] The present invention also provides a carbon monoxide selective oxidation catalyst obtained by the above molding preparation method.
[0022] Compared with the prior art, the present invention provides a molding preparation method for a carbon monoxide selective oxidation catalyst, comprising the following steps: A) mixing a carbon monoxide selective oxidation catalyst, sesbania powder and water to obtain a mixed material; B) mixing pseudo-boehmite powder and an inorganic acid solution to obtain a binder; C) mixing the binder with the mixed material to obtain a catalyst precursor; D) extruding, molding, drying and roasting the catalyst precursor to obtain a molded catalyst. The present invention first prepares a catalyst slurry, and then mixes it with a binder prepared from pseudo-boehmite and an inorganic acid solution for molding. This method can protect the original structure of the catalyst and maintain the activity of the catalyst. The method is simple to operate, has a high molding rate, and the obtained catalyst has high strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 These are the stability results of the catalyst prepared in Example 1. DETAILED DESCRIPTION
[0024] The present invention provides a method for preparing a carbon monoxide selective oxidation catalyst, comprising the following steps:
[0025] A) mixing a carbon monoxide selective oxidation catalyst, sesbania powder and water to obtain a mixed material;
[0026] B) mixing pseudo-boehmite powder and an inorganic acid solution to obtain a binder;
[0027] C) mixing the binder with the mixed material to obtain a catalyst precursor;
[0028] D) extruding the catalyst precursor into a molded catalyst, drying and calcining the catalyst precursor to obtain a molded catalyst.
[0029] The invention firstly mixes a carbon monoxide selective oxidation catalyst, sesbania powder and water to obtain a mixed material.
[0030] Wherein, the carbon monoxide selective oxidation catalyst is selected from Pt / CeO2 catalyst. The present invention has no special restrictions on the source of the Pt / CeO2 catalyst, which can be prepared by itself or a commercial product.
[0031] The mass ratio of the carbon monoxide selective oxidation catalyst to the sesbania powder is 1:(0.01-0.05), and can be 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, or any value in between 1:(0.01-0.05), and is more preferably 1:0.03.
[0032] The mass ratio of the carbon monoxide selective oxidation catalyst to water is 1:(0.1-0.25), and can be 1:0.1, 1:0.13, 1:0.15, 1:0.17, 1:0.19, 1:0.2, 1:0.21, 1:0.23, 1:0.25, or any value between 1:(0.1-0.25), preferably 1:0.15.
[0033] The present invention has no particular limitation on the mixing method, and any method of mixing raw materials known to those skilled in the art can be used. In the present invention, mixing is preferably performed by kneading.
[0034] The invention mixes pseudo-boehmite powder and inorganic acid solution to obtain a binder.
[0035] Wherein, the inorganic acid solution is hydrochloric acid, nitric acid, sulfuric acid, preferably nitric acid. Compared with other inorganic acid solutions, nitric acid solution can be removed better and does not remain in the catalyst.
[0036] The nitric acid concentration is 0.1-3 mol / L, and can be 0.1, 0.3, 0.5, 0.7, 0.9, 1, 1.5, 2, 2.5, 3, or any value between 0.1 and 3 mol / L, and the preferred concentration is 0.3 mol / L.
[0037] The mass ratio of the pseudo-boehmite powder to the inorganic acid solution is 1:(0.05-1), and can be 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, or any value between 1:(0.05-1), and the preferred ratio is 1:0.1.
[0038] The present invention has no special restriction on the preparation order of the mixed material and the binder.
[0039] After obtaining the binder and the mixed material, the binder and the mixed material are mixed to obtain a catalyst precursor.
[0040] The present invention has no special limitation on the mixing method. Preferably, the present invention slowly adds the binder into the mixed material under stirring, kneads the mixture evenly, and obtains the catalyst precursor.
[0041] The mass ratio of the mixture to the binder is 1:(0.1-0.5), and can be 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, or any value between 1:(0.1-0.5), and the preferred ratio is 1:0.2.
[0042] After the catalyst precursor is obtained, the catalyst precursor is extruded, shaped, dried and calcined to obtain a shaped catalyst.
[0043] In the present invention, there is no particular limitation on the specific methods of extrusion molding, drying and calcining, and any method known to those skilled in the art may be used.
[0044] Preferably, the drying temperature is 30-100°C, and can be 30, 40, 50, 60, 70, 80, 90, 100, or any value between 30 and 100°C, and the preferred temperature is 50°C.
[0045] The calcination temperature is 400-700°C, and can be 400, 450, 500, 550, 600, 650, 700, or any value between 400 and 700°C. The preferred calcination temperature is 500°C. The heating rate is 0.5-3°C / min, and can be 0.5, 1, 1.5, 2, 2.5, 3, or any value between 0.5 and 3°C / min, and is preferably 1°C / min. The calcination time is 2-6h, and can be 2, 3, 4, 5, 6, or any value between 2 and 6h, and is preferably 3h.
[0046] The present invention also provides a carbon monoxide selective oxidation catalyst obtained by the above molding preparation method. The carbon monoxide selective oxidation catalyst provided by the present invention has high strength and high catalytic activity.
[0047] The present invention also provides an application of the carbon monoxide selective oxidation catalyst in the elimination of carbon monoxide in a hydrogen purification system of a methanol reforming fuel cell.
[0048] The present invention first prepares catalyst slurry, and then mixes it with a binder prepared from pseudo-boehmite and an inorganic acid solution for molding. This method can protect the original structure of the catalyst and maintain the activity of the catalyst. The method is simple to operate, has a high molding rate, and the obtained catalyst has high strength.
[0049] In order to further understand the present invention, the molding preparation method of the carbon monoxide selective oxidation catalyst provided by the present invention is described below in conjunction with examples, and the protection scope of the present invention is not limited by the following examples.
[0050] Example 1
[0051] (1) Take 100 g of Pt / CeO2 catalyst, add 3 g of sesbania powder, put into a mixer and mix thoroughly. During the mixing process, add 15 ml of deionized water at a uniform rate, continue to mix and knead evenly, and obtain a wet mixed material A.
[0052] (2) Take 50 g of pseudo-boehmite powder, add 5 ml of 0.3 mol / L nitric acid solution, and stir well to obtain binder B.
[0053] (3) Add 20 g of binder B to 100 g of the mixed material A, and send the mixture into a kneader and knead for more than 3 times until it is completely mixed to obtain a molding raw material C. The raw material C is sent to an extruder, using a cylindrical perforated plate with a diameter of 1-2 mm, the extruder speed is 100 rpm, and a strip cutter is used to control the length of the extruded catalyst to 2 mm.
[0054] (4) The extruded strip catalyst was placed in a cool and dry place to dry naturally for 24 hours, and then transferred to a 50°C forced air drying oven for drying for 12 hours. Finally, the catalyst was placed in a muffle furnace and heated to 500°C at a heating rate of 1°C / min for calcination for 3 hours to obtain the final catalyst, which was recorded as HNO3-0.3.
[0055] Example 2
[0056] (1) Take 100 g of Pt / CeO2 catalyst, add 3 g of sesbania powder, put into a mixer and mix thoroughly. During the mixing process, add 15 ml of deionized water at a uniform rate, continue to mix and knead evenly, and obtain a wet mixed material A.
[0057] (2) Take 50 g of pseudo-boehmite powder, add 5 ml of 0.1 mol / L nitric acid solution, and stir well to obtain binder B.
[0058] (3) Add 20 g of binder B to 100 g of the mixed material A, and send the mixture into a kneader and knead for more than 3 times until it is completely mixed to obtain a molding raw material C. The raw material C is sent to an extruder, using a cylindrical perforated plate with a diameter of 1-2 mm, the extruder speed is 100 rpm, and a strip cutter is used to control the length of the extruded catalyst to 2 mm.
[0059] (4) The extruded strip catalyst was placed in a cool and dry place to dry naturally for 24 hours, and then transferred to a 50°C forced air drying oven for drying for 12 hours. Finally, the catalyst was placed in a muffle furnace and heated to 500°C at a heating rate of 1°C / min for calcination for 3 hours to obtain the final catalyst, which was recorded as HNO3-0.1.
[0060] Example 3
[0061] (1) Take 100 g of Pt / CeO2 catalyst, add 3 g of sesbania powder, put into a mixer and mix thoroughly. During the mixing process, add 15 ml of deionized water at a uniform rate, continue to mix and knead evenly, and obtain a wet mixed material A.
[0062] (2) Take 50 g of pseudo-boehmite powder, add 5 ml of 0.5 mol / L nitric acid solution, and stir well to obtain binder B.
[0063] (3) Add 20 g of binder B to 100 g of the mixed material A, and send the mixture into a kneader and knead for more than 3 times until it is completely mixed to obtain a molding raw material C. The raw material C is sent to an extruder, using a cylindrical perforated plate with a diameter of 1-2 mm, the extruder speed is 100 rpm, and a strip cutter is used to control the length of the extruded catalyst to 2 mm.
[0064] (4) The extruded strip catalyst was placed in a cool and dry place to dry naturally for 24 hours, and then transferred to a 50°C forced air drying oven for drying for 12 hours. Finally, the catalyst was placed in a muffle furnace and heated to 500°C at a heating rate of 1°C / min for calcination for 3 hours to obtain the final catalyst, which was recorded as HNO3-0.5.
[0065] Example 4
[0066] (1) Take 100 g of Pt / CeO2 catalyst, add 3 g of sesbania powder, put into a mixer and mix thoroughly. During the mixing process, add 15 ml of deionized water at a uniform rate, continue to mix and knead evenly, and obtain a wet mixed material A.
[0067] (2) Take 50 g of pseudo-boehmite powder, add 5 ml of 1 mol / L nitric acid solution, and stir well to obtain binder B.
[0068] (3) Add 20 g of binder B to 100 g of the mixed material A, and send the mixture into a kneader and knead for more than 3 times until it is completely mixed to obtain a molding raw material C. The raw material C is sent to an extruder, using a cylindrical perforated plate with a diameter of 1-2 mm, the extruder speed is 100 rpm, and a strip cutter is used to control the length of the extruded catalyst to 2 mm.
[0069] (4) The extruded strip catalyst was placed in a cool and dry place to dry naturally for 24 hours, and then transferred to a 50°C forced air drying oven for drying for 12 hours. Finally, the catalyst was placed in a muffle furnace and heated to 500°C at a heating rate of 1°C / min for calcination for 3 hours to obtain the final catalyst, which was recorded as HNO3-1.
[0070] Example 5
[0071] (1) Take 100 g of Pt / CeO2 catalyst, add 3 g of sesbania powder, put into a mixer and mix thoroughly. During the mixing process, add 15 ml of deionized water at a uniform rate, continue to mix and knead evenly, and obtain a wet mixed material A.
[0072] (2) Take 50 g of pseudo-boehmite powder, add 5 ml of 3 mol / L nitric acid solution, and stir well to obtain binder B.
[0073] (3) Add 20 g of binder B to 100 g of the mixed material A, and send the mixture into a kneader and knead for more than 3 times until it is completely mixed to obtain a molding raw material C. The raw material C is sent to an extruder, using a cylindrical perforated plate with a diameter of 1-2 mm, the extruder speed is 100 rpm, and a strip cutter is used to control the length of the extruded catalyst to 2 mm.
[0074] (4) The extruded strip catalyst was placed in a cool and dry place to dry naturally for 24 hours, and then transferred to a 50°C forced air drying oven for drying for 12 hours. Finally, the catalyst was placed in a muffle furnace and heated to 500°C at a heating rate of 1°C / min for calcination for 3 hours to obtain the final catalyst, which was recorded as HNO3-3.
[0075] Example 6
[0076] (1) Take 100 g of Pt / CeO2 catalyst, add 3 g of sesbania powder, put into a mixer and mix thoroughly. During the mixing process, add 15 ml of deionized water at a uniform rate, continue to mix and knead evenly, and obtain a wet mixed material A.
[0077] (2) Take 50 g of pseudo-boehmite powder, add 5 ml of 0.3 mol / L hydrochloric acid solution, and stir well to obtain binder B.
[0078] (3) Add 20 g of binder B to 100 g of the mixed material A, and send the mixture into a kneader and knead for more than 3 times until it is completely mixed to obtain a molding raw material C. The raw material C is sent to an extruder, using a cylindrical perforated plate with a diameter of 1-2 mm, the extruder speed is 100 rpm, and a strip cutter is used to control the length of the extruded catalyst to 2 mm.
[0079] (4) The extruded strip catalyst was placed in a cool and dry place to dry naturally for 24 hours, and then transferred to a 50°C forced air drying oven for drying for 12 hours. Finally, the catalyst was placed in a muffle furnace and heated to 500°C at a heating rate of 1°C / min for calcination for 3 hours to obtain the final catalyst, which was recorded as HCl-0.3.
[0080] Example 7
[0081] (1) Take 100 g of Pt / CeO2 catalyst, add 3 g of sesbania powder, put into a mixer and mix thoroughly. During the mixing process, add 15 ml of deionized water at a uniform rate, continue to mix and knead evenly, and obtain a wet mixed material A.
[0082] (2) Take 50 g of pseudo-boehmite powder, add 5 ml of 0.3 mol / L sulfuric acid solution, and stir well to obtain binder B.
[0083] (3) Add 20 g of binder B to 100 g of the mixed material A, and send the mixture into a kneader and knead for more than 3 times until it is completely mixed to obtain a molding raw material C. The raw material C is sent to an extruder, using a cylindrical perforated plate with a diameter of 1-2 mm, the extruder speed is 100 rpm, and a strip cutter is used to control the length of the extruded catalyst to 2 mm.
[0084] (4) The extruded strip catalyst was placed in a cool and dry place to dry naturally for 24 hours, and then transferred to a 50°C forced air drying oven for drying for 12 hours. Finally, the catalyst was placed in a muffle furnace and heated to 500°C at a heating rate of 1°C / min for calcination for 3 hours to obtain the final catalyst, which was recorded as H2SO4-0.3.
[0085] Comparative Example 1
[0086] (1) Take 100 g of Pt / CeO2 catalyst, add 3 g of sesbania powder, 20 g of pseudo-boehmite and 2 ml of 0.3 mol / L nitric acid solution into a mixer and mix thoroughly. During the mixing process, add 15 ml of deionized water at a uniform rate and continue to knead evenly to obtain a wet material A.
[0087] (3) Feed material A into an extruder, use a cylindrical perforated plate with a diameter of 1-2 mm, the speed of the extruder is 100 rpm, and a strip cutter is used to control the length of the extruded catalyst to 2 mm.
[0088] (4) The extruded strip catalyst was placed in a cool and dry place to dry naturally for 24 hours, and then transferred to a 50°C forced air drying oven for drying for 12 hours. Finally, the catalyst was placed in a muffle furnace and heated to 500°C at a heating rate of 1°C / min for calcination for 3 hours to obtain the final catalyst, which was recorded as HNO3-0.3-full mixture.
[0089] Comparative Example 2
[0090] (1) Take 100 g of Pt / CeO2 catalyst, add 3 g of sesbania powder, 20 g of pseudo-boehmite and 2 ml of 0.3 mol / L sulfuric acid solution into a mixer and mix thoroughly. During the mixing process, add 15 ml of deionized water at a uniform rate and continue to mix evenly to obtain a wet material A.
[0091] (2) Feeding raw material A into an extruder, using a cylindrical perforated plate with a diameter of 1-2 mm, the extruder speed is 100 rpm, and a strip cutter is used to control the length of the extruded catalyst to 2 mm.
[0092] (3) The extruded strip catalyst was placed in a cool and dry place to dry naturally for 24 hours, and then transferred to a 50°C forced air drying oven for drying for 12 hours. Finally, the catalyst was placed in a muffle furnace and heated to 500°C at a heating rate of 1°C / min for 3 hours to obtain the final catalyst, which was recorded as H2SO4-0.3-full mixture.
[0093] Comparative Example 3
[0094] (1) Take 100 g of Pt / CeO2 catalyst, add 3 g of sesbania powder, 20 g of pseudo-boehmite and 2 ml of 0.3 mol / L hydrochloric acid solution into a mixer and mix thoroughly. During the mixing process, add 15 ml of deionized water at a uniform rate and continue to mix evenly to obtain a wet material A.
[0095] (2) Feeding raw material A into an extruder, using a cylindrical perforated plate with a diameter of 1-2 mm, the extruder speed is 100 rpm, and a strip cutter is used to control the length of the extruded catalyst to 2 mm.
[0096] (3) The extruded strip catalyst was placed in a cool and dry place to dry naturally for 24 hours, and then transferred to a 50°C forced air drying oven for drying for 12 hours. Finally, the catalyst was placed in a muffle furnace and heated to 500°C at a heating rate of 1°C / min for calcination for 3 hours to obtain the final catalyst, which was recorded as HCl-0.3-full mix.
[0097] Experimental Example 1
[0098] The particle strength test was performed on all the prepared catalysts. Specifically, the crushing strength of the catalysts was measured using a particle strength tester. The results are shown in Table 1.
[0099] Table 1 Particle strength results of various embodiments and comparative examples
[0100] Catalyst name Particle strength (N / particle) Example 1 <![CDATA[HNO3-0.3]]> 64.5 Example 2 <![CDATA[HNO3-0.1]]> 28.4 Example 3 <![CDATA[HNO3-0.5]]> 65.1 Example 4 <![CDATA[HNO3-1]]> 67.1 Example 5 <![CDATA[HNO3-3]]> 70.2 Example 6 HCl-0.3 57.6 Example 7 <![CDATA[H2SO4-0.3]]> 61.8 Comparative Example 1 <![CDATA[HNO3-0.3-Full Mix]]> 44.6 Comparative Example 2 <![CDATA[H2SO4 - 0.3 - Fully Mixed]]> 45.4 Comparative Example 3 HCl-0.3-Fully mixed 48.7
[0101] It can be seen from Table 1 that, compared with the traditional method, the strength of the molded catalyst particles prepared by this method is 64.5N / particle, which is strong and can be used in complex environments.
[0102] Experimental Example 2
[0103] A certain amount of catalyst was placed in the constant temperature section of a fixed bed reactor with an inner diameter of 7 mm, and the CO selective oxidation catalytic performance of the catalysts prepared in Examples 1-7 of the present application and Comparative Documents 1-3 was evaluated.
[0104] The process conditions of CO selective oxidation reaction are as follows: reaction pressure is atmospheric pressure, reaction raw gas composition is 60% H2+1% CO+1% O2+20% CO2+18% H2O, catalyst loading is 0.3g, mass space velocity is 20000ml·g -1·h -1 The product analysis was performed using a gas chromatograph. The temperature range ΔT at which the catalyst achieves complete CO conversion (conversion rate of about 100%) and the minimum CO complete conversion temperature T 100 See Table 2.
[0105] Table 2 Results of Examples and Comparative Examples
[0106]
[0107]
[0108] From the test results in Table 2, it can be seen that the molded catalyst prepared by the present invention has the lowest temperature for achieving complete CO conversion during the catalytic CO-PROX reaction, and the widest temperature range for achieving complete CO conversion, and can achieve 100% CO conversion within 80-200°C.
[0109] Experimental Example 3
[0110] This experimental example is to test the catalytic stability of the catalyst prepared in Example 1.
[0111] A certain amount of catalyst was placed in the constant temperature section of a fixed bed reactor with an inner diameter of 7 mm, and the catalytic performance of the catalyst of the present application was evaluated for CO selective oxidation.
[0112] The process conditions of CO selective oxidation reaction are as follows: reaction pressure is atmospheric pressure, reaction raw gas composition is 60% H2+1% CO+1% O2+20H2O+17% CO2, catalyst loading is 0.3g, mass space velocity is 20000ml·g -1 ·h -1 The product analysis was performed by gas chromatography. The catalyst stability is shown in Figure 1 , Figure 1 This is the stability result of Example 1. At a reaction temperature of 150° C., the CO conversion rate of the catalyst was maintained at 100% within 500 h, and after a long period of operation, the CO concentration at the reaction outlet was less than 0.2 ppm.
[0113] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a carbon monoxide selective oxidation catalyst, characterized in that: The following steps are involved: A) mixing a carbon monoxide selective oxidation catalyst, sesbania powder and water to obtain a mixed material; B) mixing pseudo-boehmite powder and an inorganic acid solution to obtain a binder; C) mixing the binder with the mixed material to obtain a catalyst precursor; D) extruding the catalyst precursor into a molded catalyst, drying and calcining the catalyst precursor to obtain a molded catalyst.
2. The molding preparation method according to claim 1, characterized in that: The carbon monoxide selective oxidation catalyst is selected from Pt / CeO2 catalyst.
3. The molding preparation method according to claim 1, characterized in that: The mass ratio of the carbon monoxide selective oxidation catalyst to the sesbania powder is 1:(0.01-0.05), and more preferably 1:0.
03.
4. The molding preparation method according to claim 1, characterized in that: The mass ratio of the carbon monoxide selective oxidation catalyst to water is 1:(0.1-0.25), preferably 1:0.
15.
5. The molding preparation method according to claim 1, characterized in that: The inorganic acid solution is hydrochloric acid, nitric acid, or sulfuric acid, preferably nitric acid; The nitric acid concentration is 0.1-3 mol / L, preferably 0.3 mol / L.
6. The molding preparation method according to claim 1, characterized in that: The mass ratio of the pseudo-boehmite powder to the inorganic acid solution is 1:(0.05-1), and the preferred ratio is 1:0.
1.
7. The molding preparation method according to claim 1, characterized in that: The mass ratio of the mixture to the binder is 1:(0.1-0.5), and the preferred ratio is 1:0.
2.
8. The molding preparation method according to claim 1, characterized in that: The drying temperature is 30-100°C, preferably 50°C.
9. The molding preparation method according to claim 1, characterized in that: The calcination temperature is 400-700° C., preferably 500° C.; the heating rate is 0.5-3° C. / min., preferably 1° C. / min., and the calcination time is 2-6 h., preferably 3 h.
10. A carbon monoxide selective oxidation catalyst obtained by the molding preparation method according to any one of claims 1 to 9.